Multivariate assessment of site of lingual nerve. Issue 4 (April 2015) - Dias, G.J.; de Silva, R.K.; Shah, T.; Sim, E.; Song, N.; Colombage, S.; Cornwall, J.
Abstract Injury to the lingual nerve can cause debilitating symptoms. The nerve lies in the retromolar region and its anatomical site can vary within patients and according to sex, age, and dentate status. To our knowledge, no previous studies have recorded its course from multiple bony landmarks and examined the association between age, dentate status, and sex, in the same sample. We dissected 30 white cadavers and took primary and secondary reference points from the internal oblique ridge. We measured the distance to the lingual nerve in sagittal, vertical, and horizontal planes, and recorded the position where the nerve was closest to the lingual plate. We dissected 46 hemimandibles (23 male, mean age 79 years, range 52–100) of which 26 were from the left side. Mean (SD) sagittal, vertical, and horizontal distances from the primary reference point were 9.29 (3.41) mm, 9.15 (3.87) mm, and 0.57 (0.56) mm, respectively. Mean (SD) vertical and horizontal distances from the secondary point were 7.79 (5.45) mm and 0.59 (0.64) mm, respectively. The proximity of the nerve to the lingual plate varied widely (range −13.00 to 15.17 mm from the primary reference point). Dentate status was significant for the sagittal measurement from the primary point, and the vertical measurement from the secondary point. Differences in age, sex, or site of the contralateral nerve were not significant (n = 16 pairs). Our findings suggest that the site of the nerve is consistent between and within subjects for sex and age, but not for dentate status. The association between the nerve and the lingual plate varied, which suggests that care must be taken when operating in the area.